Penultimate Glacial Cycle glacier extent in the Iberian Peninsula: new evidence from the Serra da Estrela (Central System, Portugal) - Vieira, Gonçalo (2021)
The objective of this work is to present a first assessment on the age of the glacial features of the Serra da Estrela, in the central Portugal, Iberian Peninsula (40°19′ N, 7°37′ W, 1993 m), using Cosmic-Ray Exposure dating (in situ cosmogenic 36Cl). A total of 6 samples were dated, 4 extracted from exposed moraine boulders and 2 from glacially polished bedrock surfaces. Despite the low number of samples, the results are consistent, reinforcing previous dating obtained by other methods and geomorphological and paleoclimatic information. The maximum extension of the glaciers occurred at the end of the Penultimate Glacial Cycle (Marine Isotope Stage 6), during Heinrich Stadial 11, around 140 ka. At the end of the Last Glacial Cycle, slightly before the Last Glacial Maximum, at around 30 ka, the Estrela glaciers reached again a similar extent. Finally, the glaciers disappeared fromthe Serra da Estrela at the beginning of the Bølling-Allerød Interstadial, at around 14.2 ka. These data confirm a certain synchronicity in the major glacial phases in most the Mediterranean and also European mountains, although there are notable differences in the maximum extent in the two cycles.